(untitled) (DARYAFT, 2023)
BS is the main phase of Pakistan’s education system. Major portion of the higher education-seeking students reach this level of education. That is why, it carries much importance in the system. Its curriculum is going under continuous observation and consequent changes. Curriculum of BS Urdu also underwent three times changes since 2009. The curriculum was first developed by HEC in 2009. It was modified and updated in 2013. “The Undergraduate Education Policy 2020” is the latest document in this connection. The policy was issued to update the curriculum and conform it to the modern world needs. Practical and Job-oriented approach is the main focus of this policy which reflects in the nine weeks compulsory Standard Internship and entrepreneurship. In this article, the major changes and modifications suggested through this policy have been analyzed and the subsequent conclusion and recommendations have been presented.